Evaluation of small nerve fiber dysfunction in type 2 diabetes. (9th October 2019) - Ekman, Linnéa; Thrainsdottir, Soley; Englund, Elisabet; Thomsen, Niels; Rosén, Ingmar; Hazer Rosberg, Derya Burcu; Petersson, Jesper; Eriksson, Karl‐Fredrik; Dahlin, Lars B.
Abstract : Objectives: To assess potential correlations between intraepidermal nerve fiber densities (IENFD), graded with light microscopy, and clinical measures of peripheral neuropathy in elderly male subjects with normal glucose tolerance (NGT), impaired glucose tolerance (IGT), and type 2 diabetes (T2DM), respectively. Materials and methods: IENFD was assessed in thin sections of skin biopsies from distal leg in 86 men (71‐77 years); 24 NGT, 15 IGT, and 47 T2DM. Biopsies were immunohistochemically stained for protein gene product (PGP) 9.5, and intraepidermal nerve fibers (IENF) were quantified manually by light microscopy. IENFD was compared between groups with different glucose tolerance and related to neurophysiological tests, including nerve conduction study (NCS; sural and peroneal nerve), quantitative sensory testing (QST), and clinical examination (Total Neuropathy Score; Neuropathy Symptom Score and Neuropathy Disability Score). Results: Absent IENF was seen in subjects with T2DM (n = 10; 21%) and IGT (n = 1; 7%) but not in NGT. IENFD correlated weakly negatively with HbA1c ( r = −.268, P = .013) and Total Neuropathy Score ( r = −.219, P = .042). Positive correlations were found between IENFD and sural nerve amplitude ( r = .371, P = .001) as well as conduction velocity of both the sural ( r = .241, P = .029) and peroneal nerve ( r = .258, P = .018). Proportions of abnormal sural nerve amplitude became significantly higher with decreasing IENFD. No correlation was found with QST. Inter‐rater reliability of IENFD assessment was good (ICC = 0.887). Conclusions: Signs of neuropathy are becoming more prevalent with decreasing IENFD. IENFD can be meaningfully evaluated in thin histopathological sections using the presented technique to detect neuropathy.